SUASANA SHOPPING CENTER DALAM MEMBANTU MENINGKATKAN PENGALAMAN RUANG BAGI DISABILITAS SENSORIK - Almas, Puspa Alifah; Wulandari, Ratri (Universitas Mercu Buana, 2022)
The problem of sensory disability is the ability to stimulate the senses that do not function properly. The shopping center as a public space is a place that can be used for everyone but doesn’t respond to the obstacles experienced by sensory disability. This study aims to provide information and recommendations regarding the design of shopping centers with a sensory approach to create a space experience based on their perspective. The analysis of the qualitative study was conducted by comparing the literature study on the design of a community center for the blind and deaf as a research method. The result of this research is the application of interior elements with a sensory approach can be implemented to improve the spatial experience of people with sensory disabilities in the shopping center. These results can also be accepted and used in a wider community. Based on this research, it can be used as a reference for optimizing shopping centers as public spaces that can answer the problems experienced by sensory disability.